Transformation of Innovation Processes and Socio-Cultural Specificity of South Korea in the framework of the Fourth Industrial Revolution - T. V. Pospelova; A. B. Yarygina (Модернизация, инновация, развитие, 2019)
Purpose: the main purpose of this article is to explore the specific characteristics of the innovation development of South Korea. To achieve this goal the following tasks must be solved in the article: research the main principles and steps in the development of South Korea; identify and analyze the successful factors of the South Korean «economic miracle» that will continue contributing to the development and growth of the country; describe the cultural and organizational factors limiting the speed of transformation of South Korea under the fourth industrial revolution.Methods: the main methods of the research are system, structural and qualitative analyses. For the study, statistical data and articles in Russian and foreign scientific and analytical publications were used. The article is contributed with the empirical findings from the case study conducted during direct involvement of the authors in one of the industrial companies of South Korea.Results: an in-depth analyses of the transformation periods during the innovation development of South Korea was carried out, which made it possible to formulate the conclusion about existing barriers originated in the organisational approaches used to achieve the former industrial success. The problems constraining the new paradigm shift are analyzed.Conclusions and Relevance: the materials stated in the article show that in modern conditions, transition of South Korea towards Industry 4.0 is constrained by several unique factors, that used to be the key success elements in the former stages of the innovation development of the country. The research conducted in this article represents the value to the activities of various organizations interested in the innovation development, especially for development of innovation policies from the aspect of the importance of oranisational and cultural behavior at a national level. Practical application of the suggested conclusions allows hierarchical and monocultural organisations to transition to the Industry 4.0 with the consideration of important economic and social dynamics.